Design of an antenna system for the VHF communication link on the Sunsat micro satellite - Bornman, N. J. J.(Nicolaas Johannes Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1993.